Assembly Priorities in the Era of modernization of Education Reminisce (Review of quality, commentary and Hadith text content assemblies dhikr) - Ana Cahayani Fatimah; Sampara Palili (International Journal on Advanced Science, Education, and Religion, 2018)
This article examines the priority focus of discussion in the Council Dhikr with anyone who narrated about Dhikr Majlis virtue , How takhrij and i'tibar sanad hadith about the virtues Dhikr Majlis And How content (sermon) Hadith about Dhikr Majlis virtue. The method used to answer the focus of the study is a library with researcusing a normative approach that emphasizes the descriptive analysis of the data sources were found. The results showed that the hadith is narrated by (1)al-Bukhariy (2) Muslims and (3) Ahmad Bin Hanbal. The chain of 3 mukharrij through five lanes of chains with all four met in tabaqah to behold from the Bahz of Suhail of facet of Abu Huraira. takhrij activities and I'tibar of Ahmad bin Hanbal path carefully, found the transmitters of the chain as follows: (1) Abu Huraira as the last chain of narrators first (2) facet as both narrator chain V, (3) Suhail as a third narrator chain IV, (4) behold a fourth chain of narrators III (5) Affan as the fifth chain of narrators II and (6) Ahmad bin Hanbal as well as the last narrator al-Mukharrij al-Hadith. secar implicit when observed honor traditions of Ahmad ibn Hanbal, coming from Yahya ibn Sa'id from 'Abdallah ibn Sa'eed Mawla of Abi Ziyad Abu Ayyash from Darda' that the Prophet it to my question as to the content of the question is the Messenger of Allah said: "Shall I show you do the best, the most holy in the sight of your king (God), and the lifting derajatmu; be better for you than gold or silver, and better for you than meeting your enemies-in, and then you cut off his head or they cut your throat". The Companions who were present said: "What this is Ya Allah!". He said: "Remembrance of Allah, the most Exalted, the Most Great".